Ivabradine improves left ventricular twist and untwist during chronic hypertension. (1st February 2018) - Jozwiak, Mathieu; Melka, Jonathan; Rienzo, Mario; Bizé, Alain; Sambin, Lucien; Hittinger, Luc; Berdeaux, Alain; Su, Jin Bo; Bouhemad, Belaid; Ghaleh, Bijan
Abstract: Background: Left ventricular (LV) dysfunction develops during LV hypertrophy and particularly during tachycardia. Thus we investigated the effects of heart rate (HR) reduction with ivabradine, an I f -channel blocker, on LV twist and untwist which represents myocardial deformation occurring during the overall systole and diastole and therefore provide valuable evaluation of global LV systolic and diastolic function. Methods: Eight chronically instrumented pigs receiving continuous angiotensin II infusion during 28 days to induce chronic hypertension and LV hypertrophy. Measurements were performed at Days 0 and 28 after stopping angiotensin II infusion in the presence and absence of ivabradine. Results: At Day 0, reducing HR from 75 ± 3 to 55 ± 2 beats/min with ivabradine did not affect LV twist but slowed LV untwist along with an increase in LV end-diastolic pressure. At Day 28, LV posterior and septal wall thickness as well as the estimated LV mass increased, indicating LV hypertrophy. LV twist and untwist were significantly reduced by 33 ± 4% from 16 ± 1° and 32 ± 6% from − 154 ± 9°/s, respectively, showing global LV systolic and diastolic dysfunction. In this context, ivabradine decreased HR by 25% from 86 ± 5 beats/min and significantly improved LV twist from 11 ± 1 to 14 ± 1° and LV untwist from − 104 ± 8 to − 146 ± 5°/s. Conclusions: Administration of ivabradine during chronic hypertension and LV hypertrophy improved LV twist and untwist. This further supports the beneficial effect of this drug on both LV systolic and diastolic function during the development of LV hypertrophy.